Depression, self-concept, future expectations and hope of people with HIV. - Freire de Araújo Patrício, Anna Cláudia; Bergmam do Nascimento Silva, Ingrid; Azevedo Minhaqui Ferreira, Milenna; Feitosa Lopes Rodrigues, Brenda; Ferreira da Silva, Rôseane; Agnaldo do Nascimento, João; Rosendo da Silva, Richardson Augusto (Revista Brasileira de Enfermagem)
Objective: To analyze conditions of depression, self-concept, future expectations and hope in people with HIV/AIDS. Method: Cross-sectional survey of 108 individuals living with HIV/AIDS, carried out in a reference hospital for the treatment of infectious diseases in Northeast Brazil. The following instruments were employed: sociodemographic data, and questionnaires for ascertaining participants' emotions, including scales for self-concept, hope, depression (HAMD-D), and future expectations. Descriptive statistics using the following tests were performed: Mann-Whitney, Kruskal-Wallis, chi-square, and t-test--considered significant when p < 0.05. Results: 31.5% presented mild depression and 21.3% presented moderate depression; 63% reported difficulty in obtaining decent employment; 52.8% considered life a failure; 52.8% felt worthless. Fear, guilt and loneliness influenced self-concept (p < 0.05). Loneliness influenced hope (p < 0.05). Conclusion: It is necessary to raise the attention of nursing professionals and healthcare managers to the importance of providing health services that consider the mental health of people with HIV/AIDS, contributing to treatment adherence and well-being.